2016
DOI: 10.1590/2236-8906-59/2015
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia foliar de Rubiaceae ocorrentes em fragmento florestal urbano de Mata Atlântica, PR, Brasil

Abstract: -(Foliar anatomy of Rubiaceae occurring in an urban forest fragment of Atlantic Forest, Paraná State, Brazil). Rubiaceae in Brazil occurs mainly in the Atlantic Forest biome that in the southern region is represented by two main vegetation types: Seasonal Semi-deciduous Forestand Araucaria Forest. Both occur in the Ecological Park Paul Gorski (PEPG), an urban forest fragment. Given the relevance of Rubiaceae in the Atlantic Forest and the importance of ecological anatomy studies to understand colonization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
4
0
7
Order By: Relevance
“…In the leaves of the studied plants, the presence of accessory bundles was observed, which represent agglomerates of xylem and phloem without a defined organization, formed from the fragmentation of the main bundle borders (Mantovani, Gomes, Gomes, & Vieira, 1995). These are characteristics of some members of the genus, such as in P. carthagenensis and P. suturella (Zini et al, 2016), Irlbachia nemorosa, (Corrêa, Melo, Krahl, & Araújo, 2014). In the plants of this study, accessory bundles of concentric and anficrival conformation were always observed in pairs of 1-3, rarely presenting 4 pairs that follow the midrib longitudinally, throughout the extension of leaf lamina.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the leaves of the studied plants, the presence of accessory bundles was observed, which represent agglomerates of xylem and phloem without a defined organization, formed from the fragmentation of the main bundle borders (Mantovani, Gomes, Gomes, & Vieira, 1995). These are characteristics of some members of the genus, such as in P. carthagenensis and P. suturella (Zini et al, 2016), Irlbachia nemorosa, (Corrêa, Melo, Krahl, & Araújo, 2014). In the plants of this study, accessory bundles of concentric and anficrival conformation were always observed in pairs of 1-3, rarely presenting 4 pairs that follow the midrib longitudinally, throughout the extension of leaf lamina.…”
Section: Discussionmentioning
confidence: 93%
“…Uniseriate epidermis with cells presenting larger anticlinal walls than periclinal in the adaxial surface, where it shows varied sizes, is considered as a common characteristic in Psychotria (Metcalfe & Chalk, 1979;Quinteiro et al, 2007;Zini, Martins, Toderke, & Temponi, 2016). Idioblasts containing alkaloids, dispersed druses throughout leaf lamina, mainly in epidermis cells, were also found in species of Borreria (Zini et al, 2016). Druses have important defense role against herbivory, and according to (Franceschi & Nakata, 2005) they contribute to increase the use of light during photosynthesis in plants that grow under shade.…”
Section: Discussionmentioning
confidence: 99%
“…Epiderme unisseriada com células apresentando paredes anticlinais maiores que as periclinais na face adaxial do que na abaxial, onde apresenta tamanhos variados é considerada como uma característica comum em Psychotria (Metcalf e Chalk, 1979;Quinteiro et al, 2006;Zini et al, 2016). Idioblastos contendo alcaloides, drusas dispersas ao longo de todo o limbo foliar, principalmente em células epidérmicas, também foram encontradas em espécies de Borreria por Zini et al (2016). Drusas tem papel importante na defesa contra herbívoria e de acordo com Franceschi e Nakata ( 2005) contribuem para ampliar o aproveitamento da luz durante a fotossíntese em plantas que crescem na sombra.…”
Section: Discussionunclassified
“…Nas folhas das três populações foi observada a presença de feixes acessórios, que representam aglomerados de xilema e floema sem organização definida, formados a partir da fragmentação das extremidades do feixe principal (Mantovani et al, 1995). Estes são característicos de alguns membros do gênero, como em P. carthagenensis e P. suturella (Zini et al, 2016), Irlbachia nemorosa (Corrêa et al, 2014). Nas plantas deste estudo os feixes adicionais de conformação concêntrica e anficrival foram sempre observados em pares de 1-3, podendo apresentar raramente 4 pares que acompanham a nervura central, longitudinalmente, por toda a extensão do limbo foliar.…”
Section: Discussionunclassified
See 1 more Smart Citation